Subarachnoidally administered hyperbaric morphine, buprenorphine, methadone, and 10% dextrose on cardiopulmonary function and behavior in horses - Natalini,Cláudio Corrêa (2006)
The study was done to compare the heart rate, arterial blood pressure, arterial blood gases, respiratory rate, body temperature, and behavior after subarachnoid administration of hyperbaric morphine (MorphineD10), buprenorphine (BuprenorphineD10), methadone (Methadone D10), and 10% dextrose (D10) in conscious horses. Six adult horses were studied. Treatments were administered into the lombo-sacral subarachnoid space through an epidural catheter, MorphineD10 at 0.01mg kg-1, BuprenorphineD10 at 0.001mg kg-1, MethadoneD10 at 0.01mg kg-1, and 10% dextrose as a control group. The results showed that there are minimum changes in heart and respiratory rate, blood gases, blood pressure, and body temperature after subarachnoid administration of hyperbaric opioids in horses. No sedation and nor motor impairment or behavioral changes occur.